Behavioral Risk Profiles of Homeschooled Adolescents in the United States: A Nationally Representative Examination of Substance Use Related Outcomes. (23rd February 2017) - Hodge, David R.; Salas-Wright, Christopher P.; Vaughn, Michael G.
ABSTRACT: Background : The homeschool population continues to grow in size and now accounts for 3.4% of all students in the United States. Objective : Given the heterogeneous nature of the population, this study examines the relationship between different types of homeschoolers and a number of substance use related outcomes. Methods : To conduct this study, we used pooled data (2002–2013) from the National Survey on Drug Use and Health (NSDUH). Respondents aged 12–17 who reported they had been homeschooled at any time during the previous 12 months were classified as homeschoolers ( N = 1, 321). Latent profile analysis (LPA) was conducted to identify latent subgroups of homeschoolers and multinomial regression was executed to assess the relationship between the subgroups and perceived substance use risk, availability, and past 12-month use. Results : The LPA yielded four subgroups, which were summarized as (1) highly religious and engaged, (2) limited parental monitoring, (3) high parental warmth and support, and (4) secular permissive. Of these, the highly religious and engaged subgroup was the least likely to report using substances. Conclusion : The results underscore the variation that exists among homeschoolers and the importance of examining the relationship between different types of homeschoolers and outcomes of interest.